How and When Personalized Advertising Leads to Brand Attitude, Click, and WOM Intention. Issue 1 (25th April 2022) - De Keyzer, Freya; Dens, Nathalie; De Pelsmacker, Patrick
Abstract: We study the effect of perceived personalization in advertising on social networking sites (SNSs) on consumer brand responses. In study 1 ( N  = 202), we test a parallel mediation via perceived personal relevance and intrusiveness on brand attitude (Ab) and click intention (CI). Perceived personalization improves Ab and CI by increasing the perceived personal relevance and, unexpectedly, by decreasing the perceived intrusiveness of the ad. Study 2 ( N  = 264) extends the processing mechanism of personalized advertising by additionally including the mediating effects of self-brand connection and reactance toward the ad. Perceived personalization has a positive indirect effect on self-brand connection via perceived personal relevance, but not via perceived intrusiveness. Self-brand connection, in turn, has a positive effect on consumers' responses. Contrary to expectations, reactance does not significantly affect brand responses. Study 2 also examines the moderating role of perceived privacy protection by the SNS. Higher levels of perceived privacy protection by the SNS do not strengthen the indirect effects of perceived personalization.